Performance of boron on mung bean (Vigna radiata L.) productivity (Journal of Biodiversity Conservation and Bioresource Management, 2025)
The present investigation was performed to estimate the effect of different levels of boron on the growth and yield of mung bean (Vigna radiata L.) under AEZ-8, Manikganj district of Bangladesh. Six treatments such as T1: Control, T2: B@ 1 kgha-1 + RDF, T3: B@ 3 kgha-1 + RDF, T4: B@ 4 kgha-1 + RDF, T5: B@ 4 kgha-1 + RDF and T6: RDF (N20 P45 K30 S15 kgha-1) were designed to assess the impact. The experiment was laid out in a randomized complete block design maintaining three replications. Increasing the levels of boron significantly influences the growth, yield and yield attributes of mung bean, in the company of recommended fertilizer dose. The principal outcome of boron indicated that 3.0 kgha-1 B was superior to other doses concerning mung bean yield and yield traits. In addition, the highest grain yield increment (48.43%) over control was also achieved from 3 kg B ha-1. The tallest plant (54.55 cm), maximum no. of branches (2.68), number of pods (20), pod length (8.89 cm) and yield of stover (2.80 tha-1), 1000 seed (42.30 tha-1) and grain (1.90 tha-1) of mung bean were found with T3: B@ 3 kgha-1 and minimum in control (T1). The highest number of seeds per pod was recorded (13) in T4: B@ 4 kgha-1 + RDF. The overdose of B@ 4 and 5 kgha-1 reduces the yield of stover, 1000 seeds and grain of mung bean compared to 3 kg B ha-1 in T3. The study indicated that the integrated addition of B along with NPKS enriched the post-harvest soil by a good percentage. On the basis of the production skill, of grain yield, the treatments can be arranged in the order of T3 > T4 > T5 > T6 > T2 > T1. The application of boron @ 3 kgha-1 along with N20 P45 K30 S15 kgha-1 could be found suitable for boosting mung bean yield in AEZ-8 soils of Bangladesh.J. biodivers. conserv. bioresour. manag. 10(2), 2024: 19-30